Surgical Stabilization of Coxofemoral Luxation and BilateralFemur Fracture in a Pug by a Combination of ThreeTechniques - Jekinakatti, Kanteshkumar Mahadev; D R, Manjunatha; D, Vilas; Nagaraju, N (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Coxofemoral luxation is separation of the femoral head from the acetabulum. About 40 to 90% of all luxations  in dogs and cats are coxofemoral luxations (Venzin and  Montavon, 2007; Smitha, 2014). The amount of soft tissue  damage caused by luxation depends on the luxation’s  traumatic forces, direction and duration before therapy  (Trostel and Fox, 2020). The relationship of the femoral  head to the acetabulum after dislocation is typically used to  categorize coxofemoral luxations. They are the craniodorsal,  caudodorsal, cranioventral, caudoventral and intrapelvic  dislocation. The most frequent kind of dislocation is  craniodorsal coxofemoral luxation, which occurs in 90% of  cases (Shivakumar, 2015). The majority of canine coxofemoral  luxations have responded to external manipulation, closed  reduction and external fixation with bandages and splints  (Anoop et al., 2012). Coxofemoral luxation in dogs has been  treated with double sided toggle pin technique (Ergin et  al., 2016). Open surgical reduction enhances stability and  lessens the possibility of reluxation when compared to closed  reduction.